MOLECULAR DOCKING STUDIES OF OMP6 PROTEIN OF HAEMOPHILUS INFLUENZAE WITH PHYTOLIGANDS - SRUJANA KHANDRIKA; UDHAYA LAVINYA; RAMADEVI MOHAN; SUBHASHREE VENUGOPAL (International Journal of Pharma and Bio Sciences, 2014)
Haemophilus influenzae is an important human pathogen affecting infants and children often infecting ear and eye causing otitis media, conjunctivitis, sinus infections, pneumonia, epiglottitis and meningitis. OMP6 (Outer membrane protein 6) protein of the organism is an important antigen involved in adhesion with Toll-like receptor 2 of the host. In this study, we downloaded the 3D structure of OMP6 protein from PDB database with PDB code 2AIZ and the structure was refined by submitting to KOBAMIN server. Forty different phytoligands were identified from Pubchem compound database and the corresponding PDB files were drawn from CORINA by submitting SMILES of the compounds into the tool. Docking analysis was performed for the target protein with those ligands to study the binding interactions between them using Patchdock server. The analysis revealed that the compounds Silibinin and Silimarin with highest patchdock score of 4298 could be a potential drug lead to treat OMP6 virulence.